2011
DOI: 10.1167/iovs.11-8108
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness in Relation to Sex and Axial Length in 93 Danish University Students

Abstract: In this study of healthy young participants choroidal thickness was 18% higher in men than in women when adjusting for age and axial length. This observation may help explain the effect of sex in conditions related to choroidal thickness such as myopia, central serous chorioretinopathy, and age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
193
19
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(233 citation statements)
references
References 36 publications
19
193
19
2
Order By: Relevance
“…In a recent study of young Danish adults aged 20-29 years, the average SFCT was 344 mm. 6 Thus, our finding of a mean choroidal thickness of 327 mm in those aged [16][17][18][19] years suggests that choroidal thickness approaches the adult value at this age. Several cross-sectional studies in adults have clearly shown that choroidal thickness later decreases with advancing age; the mean decrease is 15-20 mm per decade in later life.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In a recent study of young Danish adults aged 20-29 years, the average SFCT was 344 mm. 6 Thus, our finding of a mean choroidal thickness of 327 mm in those aged [16][17][18][19] years suggests that choroidal thickness approaches the adult value at this age. Several cross-sectional studies in adults have clearly shown that choroidal thickness later decreases with advancing age; the mean decrease is 15-20 mm per decade in later life.…”
Section: Discussionmentioning
confidence: 65%
“…14 In the current study, we investigated the SFCT variations during growth period of eye and body size using spectraldomain OCT. Choroidal thickness has been measured in the various populations of healthy subjects. [4][5][6] Many recent studies have reported ocular disorders associated with altered abnormal choroidal thickness. In high myopia, retinal dystrophy, and age-related choroidal atrophy, the choroid was reported to have decreased thickness, whereas increased choroidal thickness was reported in central serous chorioretinopathy and Vogt-Koyanagi-Harada disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Large populationbased studies found significant correlation between increased age and increased axial length with decreased choroidal thickness. [30][31][32][33][34] Furthermore, the diminution in choroidal thickness with age was approximately the same in absolute quantities in highly myopic eyes as in eyes without high myopia. 35 When highly myopic eyes grow with age, the choroid may become very thin and even completely absent.…”
Section: Choroidmentioning
confidence: 78%
“…Known factors affecting choroidal thickness are age, 18,19 axial length, 19,20 specific medications, 21 and chorioretinal disorders such as central serous chorioretinopathy. 22 Patients with high myopia, 18,23 diabetic retinopathy, 24 and age-related choroidal atrophy 25 appear to have a particularly thin choroid.…”
Section: Introductionmentioning
confidence: 99%